Women's independent decision-making power and determinants on not to use contraceptives among currently married women in Ethiopia using demographic and Health Survey data: Multilevel Analysis - Desalegn Tesfa; Melkalem Mamuye Azanaw; Alemayehu Digssie Gebremariam; Melaku Tadege Engidaw; Mulu Tiruneh; Melkamu Aderajew Zemene; Denekew Tenaw Anley; Anteneh Mengist Dessie (BMC, 2022)
Abstract Background Evidence suggests that couples frequently dispute regarding the desirability of pregnancy, as well as whether or not to employ family planning measures. There are numerous unmet needs owing to partner or family objections, according to a scares study that illustrates women's independent decision-making capacity on whether or not to use a contraceptive. As a result, the purpose of this study was to analyze women's independent decision-making power and determinants of not using contraceptives. Methods Reproductive age group women aged (15-49 years) currently married who are not pregnant and are currently not using family planning preceding five years the survey was included from the individual record (IR file) file using standard demographic and health survey datasets of Ethiopia. Using multilevel logistic regression models, we investigated the relationship between several independent factors and women's independent decision-making not to use contraception. The adjusted odds ratios were evaluated using 95% confidence intervals. Results A total of 5,598 currently married women were included in this study. Individual level factors significantly associated with women independent decision making on not to use contraceptive were female-led households (AOR = 2.11; 95% CI = 1.60-2.78), being orthodox ( AOR = 1.84; 95% CI = 1.39-2.44 ) and protestant ( AOR = 1.62; 95% CI = 1.17-2.23), and belonging to more than one union (AOR = 1.48; 95% CI = 1.12-1.95). Whereas, low community education (AOR = 1.19; 95%= 1.00-1.49) and regions: in Tigray (AOR = 2.19; 95%CI = 1.51-3.16), Afar (AOR = 1.74; 95% CI = 1.14-2.64), Amhara (AOR = 2.45; 95% CI = 1.71-3.500), South Nations Nationality (AOR = 1.87; 95% CI = 1.32-2.65), Gambela (AOR = 2.58; 95% CI = 1.73-3.84), Hareri (AOR = 3.93; 95% CI = 2.62-5.88), and Dre DDewa (AOR = 1.66; 95% CI = 1.12-2.45) were community-level factors. Conclusion Women's independent decision-making power not to use contraceptives was low and greatly affected by both individual and community-level factors. Therefore, it is necessary to develop policies and create programs that promote women's empowerment by incorporating their partners in each region of the nation to encourage women's independent decision-making authority to use or not to use a contraceptive.